2010
DOI: 10.1007/s10096-010-0935-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of influenza-associated hospitalization in adults, Toronto, 2007/8

Abstract: The purpose of this investigation was to identify when diagnostic testing and empirical antiviral therapy should be considered for adult patients requiring hospitalization during influenza seasons. During the 2007/8 influenza season, six acute care hospitals in the Greater Toronto Area participated in active surveillance for laboratory-confirmed influenza requiring hospitalization. Nasopharyngeal (NP) swabs were obtained from patients presenting with acute respiratory or cardiac illness, or with febrile illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…This is consistent with other studies on 2009 pandemic influenza which found greater affinity of the novel A (H1N1) virus for the younger population [21][22][23][24][25][26][27] . The majority of the patients (79.3%) were between the age of 10 and 50 years.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with other studies on 2009 pandemic influenza which found greater affinity of the novel A (H1N1) virus for the younger population [21][22][23][24][25][26][27] . The majority of the patients (79.3%) were between the age of 10 and 50 years.…”
Section: Discussionsupporting
confidence: 92%
“…While many studies invoke bacterial overgrowth, epidemiological data suggest almost all patients receive antibiotics (13,43) and many lung cultures at autopsy are negative (11). The fact that superinfection is associated with worse outcomes despite universal prescription of antibiotics (13) suggests that superinfection-related disease might be related to an aberrant host response (44), in addition to a role for immunosuppression by the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Two participants, both in the prophylaxis group and in health care workers, dropped out before starting antiviral prophylaxis and are not included in the remaining analyses. Demographic characteristics of participants are 15 Of the 42 participants who started oseltamivir prophylaxis, 4 (10%) discontinued before 13 weeks owing to adverse effect, including: nausea (week 1), nausea and malaise (week 3), sleep disturbances (week 4) and headache (week 11). Thirty-nine of 42 participants (95%) reported taking six or seven capsules per week for the first 8 weeks; by week 12, 34 (81%) reported continuing to miss no more than one capsule per week.…”
Section: Resultsmentioning
confidence: 99%